2019
DOI: 10.1016/j.celrep.2019.04.081
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1 Represses Neural Differentiation and Cooperates with CTBP2 to Dynamically Regulate Cell Migration during Neocortex Development

Abstract: Highlights d ZEB1 is expressed in embryonic neural progenitor cells, but not in neurons d ZEB1 blocks lineage progression to neuronal commitment and cell migration d Prolonged Zeb1 expression leads to subcortical band heterotopia d ZEB1 acts synergistically with CTBP2 to regulate cell morphology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 116 publications
3
42
0
Order By: Relevance
“…Therefore, the effects of Zeb1 deletion in the brain have so far only been investigated during embryonic development. Two studies have reported that downregulation of ZEB1 expression is necessary for the neuronal commitment of precursor cells, allowing them to gain a neuronal identity while migrating to their maturation destinations in the developing cerebellum and cortex, respectively (Singh, Howell et al 2016, Wang, Xiao et al 2019. This is partially mirrored in the adult hippocampus as we observed a lack of ZEB1 in the neuroblast and granule neuron populations.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Therefore, the effects of Zeb1 deletion in the brain have so far only been investigated during embryonic development. Two studies have reported that downregulation of ZEB1 expression is necessary for the neuronal commitment of precursor cells, allowing them to gain a neuronal identity while migrating to their maturation destinations in the developing cerebellum and cortex, respectively (Singh, Howell et al 2016, Wang, Xiao et al 2019. This is partially mirrored in the adult hippocampus as we observed a lack of ZEB1 in the neuroblast and granule neuron populations.…”
Section: Discussionsupporting
confidence: 62%
“…Results ZEB1 is a known regulator of stemness in many solid tissues (Goossens, Vandamme et al 2017). Recent studies have shown that ZEB1 functions in embryonic neurogenesis (Singh, Howell et al 2016, Liu, Liu et al 2019, Wang, Xiao et al 2019), and we have previously shown that ZEB1 is crucial for the self-renewal of cancer stem cells in glioblastoma (Siebzehnrubl, Silver et al 2013, Hoang-Minh, Siebzehnrubl et al 2018, Jimenez-Pascual, Hale et al 2019.…”
Section: Zeb1 In Hippocampal Neurogenesismentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, while not playing a direct role in the regulation of the BTSC precursor state under our culture conditions, key EMT transcription factors other than SLUG likely play important roles in tumor progression by contributing to essential processes such as invasion and survival and proliferation. Interestingly, ZEB1, the most expressed EMT regulator across our BTSC lines, plays central roles in regulating differentiation and invasion in both NSCs during development and glioma cells [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…EMT was important in direct cell fate conversion in addition to reprogramming, embryonic development, and cancer progression [40]. EMT was critical for biological processes involving cell migration, such as gastrulation, neural crest delamination, and invasion and metastasis of carcinoma cells [41,42]. Interplay between autophagy and EMT influences cell fate [43].…”
Section: Discussionmentioning
confidence: 99%